Amaqaba nama Gqobhoka?: Working through Colonial Derision of Black Ontology. Issue 173 (1st December 2022) - Kumalo, Siseko H.
Abstract: Working through the two concepts of amaqaba nama gqobhoka, I outline 'ontological derision'. I argue that ontological derision is rooted in intra-Black conflict that leads to interracial conflict, and propose ontological recognition as a resolution to the tensions that exist in the South African political landscape. To reach the postcolonial condition advanced by scholars like Mahmood Mamdani (2021), the modes of life that existed in South Africa prior to colonial imposition need to be recognised as legitimate and worthy of participation in the formation of the public sphere. I argue that recognising this ontology will inform the genuine formation of an inclusive national identity in South Africa. Such a proposal is rooted in the thinking of William Wellington Gqoba, who suggests that the more the two cultures understand each other, the less tensions will exist between them.